Perception of the Divine Essence from Ayatollah Javadi Amoli's Viewpoint - Rouhollah Souri (حکمت اسرا, 2024)
The perception of the Divine essence is challenging in Islamic mysticism and philosophy. Ayatollah Javadi Amoli has a unique view on this subject matter, which has not yet been the topic of an independent study. This paper explains this kind of perception by using a descriptive-analytical method. Ayatollah Javadi Amoli considers the Divine essence to be "non-conditioned existence at the stage of division" and believes that the Divine essence is not perceptible due to indeterminableness and infiniteness. He provides reasons for the imperceptibility of the essence and holds that both acquired and intuitive knowledge have limitations in perceiving the hidden essence of the divine. He also does not accept the intuitive perception of the essence after mystical annihilation. Moreover, he does not acknowledge the perception of any part of the essence that is within the reach of the mystic, because the Divine essence is purely simple and indivisible. From his viewpoint, what can be perceived is the manifested essence, not the essence as it is in itself. The absolute Divine identity is the absolute unseen, and no one has a direct (unmediated) connection with it. This viewpoint is subject to critiques, which are discussed in this study.